(untitled) (Praxis Educativa, 2015)
This paper describes and analyzes the current status of Secondary Education in Chile. Wide coverage, mediocre performances and social inequity are revealed within a context of tradability and prominence of private institutions. Performance-Based Agreements for the improvement of teacher education at a university level are highlighted as of their novel nature. These instruments put the objectives of each University with those of the State into alignment through negotiated processes within the framework of formal contracts setting “Performances of Excellence”. These represent profound changes in both the outcomes and impacts of the quality of teacher education.